Bi-directional screening of tuberculosis patients for type 2 diabetes mellitus and diabetes patients for tuberculosis in Bhubaneswar, Odisha - Das, Shritam; Das, Elina; Bhuyan, Kashyap; Prusty, Biswajita; Barik, Minaketan; Yadav, V. S.; Hussain, Tahziba (International Journal Of Community Medicine And Public Health, 2017)
Background: The aim of the study was to assess the feasibility and results of screening diabetes mellitus (DM) patients for tuberculosis (TB) and TB patients for DM within the routine health care settings. Methods: Prospective observational study was carried out within the Diabetes Centre and TB division from June, 2014 to June, 2016. The screening for active TB in DM and DM in TB patients is followed as per the guidelines of the revised national tuberculosis control programme and national programmes in India. Results: 350 patients with active TB disease were screened for diabetes during the study period. Among the TB patients, 28% patients were having pre-diabetes and 17% patients were having diabetes. Both the conditions, pre-Diabetes or diabetes, were more common among males, married patients, advancing age, having less education, no specific job, sedentary life style, smoking / drinking, living in crowded areas, poor living conditions as well as unhygienic environment. 350 patients with diabetes were screened for TB in which 8 (2.2%) patients found to have TB. The various socio-demographic factors appeared to be significant factors. RBG levels, cholesterol and triglycerides were raised among most of the diabetes patients. Age, male gender and Cat-I status appeared to be significant factors among patients having both conditions The incidence of TB among T2DM patients is less than that reported from other regions. Conclusions: Bi-directional screening of TB patients for DM and DM patients for active TB leads to earlier detection of DM as well as TB, better TB-specific treatment, favourable outcome for TB as well as DM and prevention of DM complications. This study is the first of its kind in this State.